Investigation on the Chemical Constituents of the Leaves of Ficus elastica Roxb. and Their Antimicrobial Activity - Almahyl, Hassan Abdalla; Rahmani, Mawardi; Sukari, Mohd Aspollah; Ali, Abdul Manaf (Universiti Putra Malaysia Press, 2003)
Four known compounds (emodin, sucrose, morin and rutin) were isolated from the leaves of Ficus elastica Roxb. The structures of the compounds were established by spectroscopic techniques and by comparison with published data. The compounds were screened for antimicrobial activity against two species of bacteria, Bacillus cereus (Gram-positve) and PseuiUlmonas aeruginosa (Gram-negative) and four species of fungi by using the disc diffusion method. The compounds showed antibacterial activity but no antifungal activity was observed against the tested organisms.